1995
DOI: 10.1139/o95-023
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin activates phospholipase D through pertussis toxin-insensitive GTP-binding protein in aortic smooth muscle cells: function of Ca2+/calmodulin

Abstract: In the present study, we examined the effect of vasopressin (AVP) on phosphatidylcholine-hydrolyzing phospholipase D activity in primary cultured rat aortic smooth muscle cells. AVP stimulation of choline formation was dose dependent. The time-course was quite different from those of inositol phosphates. The effect of AVP on the formation of inositol phosphates (EC50 was 3 nM) was more potent than that on the formation of choline (EC50 was 30 nM). 12-O-Tetradecanoylphorbol-13-acetate (TPA), an activator of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Similar methods were used by Ito and colleagues (11) who also found that the release of 3 H radioactivity was stimulated by very low concentrations of AVP (EC 50 ϳ 50 pM). However, reports that AVP stimulates PLD in VSM [including A7r5 cells (13,15,23)] led us to investigate whether some of the radioactivity may be in the form of PA (the product of PLD), which may contain the labeled fatty acyl moiety. We used TLC to separate the lipid products and then determined the radioactivity that comigrates with purified AA or PA standards.…”
Section: Resultsmentioning
confidence: 99%
“…Similar methods were used by Ito and colleagues (11) who also found that the release of 3 H radioactivity was stimulated by very low concentrations of AVP (EC 50 ϳ 50 pM). However, reports that AVP stimulates PLD in VSM [including A7r5 cells (13,15,23)] led us to investigate whether some of the radioactivity may be in the form of PA (the product of PLD), which may contain the labeled fatty acyl moiety. We used TLC to separate the lipid products and then determined the radioactivity that comigrates with purified AA or PA standards.…”
Section: Resultsmentioning
confidence: 99%
“…V1a receptor is located mainly in the central nervous system and cardiovascular organs including VSMC, while V1b and V2 are located in the central nervous system and kidney, respectively. As for intracellular signaling mechanisms, it has been reported that AVP mobilizes intracellular Ca 2+ and stimulates protein kinase C (PKC) through the activation of phospholipase (PL) C and PLD in VSMC [15][16][17], which is involved in the mechanism of AVP-induced proliferation of these cells [18]. Other important signaling pathways to mediate the mitogenic and differentiation processes are tyrosine kinases.…”
mentioning
confidence: 99%
“…A plethora of GPCR agonists have been shown to stimulate PLD activity. Angiotensin II (24), bradykinin (25), carbachol (26), lysophosphatidic acid (27), gonadotropin-releasing hormone (28), vasopressin (29), endothelin (30), thyrotropin (31), and prostaglandin F 2␣ (32) are examples of the prevalent nature of GPCR-mediated stimulation of PLD. GPCRs can stimulate PLD through phospholipase C (PLC)-dependent signaling pathway.…”
Section: Somatostatin (Ss)mentioning
confidence: 99%